Investigating English Vocabulary Mastery of Students with Special Educational Needs (SEN) through Using Animated Cartoons - Irawati, Lulus; Natalia, Krismi; Arifin, Samsul (Makassar State University, 2023)
Abstract. Every student has a different ability to learn vocabulary. There are students with good ability to learn new vocabulary, but on the other side, there are also students with low ability to learn. Students who have a low ability to learn are usually called students with special education needs. They need extra consideration for their education. An animated cartoon is suggested to be one of the audiovisual media that provide both sounds and moves. This research was conducted to know the effect of using animated cartoons on the vocabulary mastery of students with special educational needs (SEN). The research was using a pre-experimental research design and the type of data was numeric data from students' tests. This research was conducted in one of the SEN schools in Madiun Regency involving 15 students with mental retardation. The data were collected by exhibiting a vocabulary mastery test. The data were analyzed by using paired sample t-test with the level of significance at.05. The result shows the significant value is 0.002. This value is lower than the α = 0.05, so Ha is accepted, and H0 is rejected. It can be said that there is a significant effect of animated cartoons on students' vocabulary. It implies that the animated cartoon can help students with special education needs especially mental retardation to learn vocabulary. Hopefully, the next researchers can conduct other research using the media for other skills and disabilities.Keywords: Animated Cartoon, Vocabulary mastery, Students with Special Education Needs